Understanding the change process: Valuing what it is that coaches do - Cassidy, T. (International Journal of Sports Science and Coaching, 2010)
When coaching is viewed as a rational process it is often assumed that coaches can reflect upon and, where necessary, change their behaviour. In this commentary, it is contended that using a rational argument to change practice is limited if consideration is not given to the way coaches learn how to coach. Knowledgeability is a generative concept for understanding why it is difficult to change time-honoured practices or day-to-day conventions that have often become taken for granted. The aims of this article are to introduce the concept of `knowledgeability` and associated `practical consciousness`, and to highlight the explanatory power of the latter for understanding the change process.